2015
DOI: 10.1055/s-0035-1554173
|View full text |Cite
|
Sign up to set email alerts
|

The Outcome of Pedicle Screw Instrumentation Removal for Chronic Low Back Pain

Abstract: Introduction There have been a limited number of small case series reporting improvement in patients' function and pain scores following removal of pedicle screw metalwork for nontraumatic lumbar fusion surgery. The investigators' aim was to determine the degree of satisfaction from a patient cohort; and improvement in pain status after removal of pedicle screw instrumentation and factors that may influence the outcome. Methods Patients who had removal of pedicle screw instrumentation for posterolateral lumbar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…The study identified that the most common localization of low back pain after instrumentation was in the sacroiliac joint, likely due to stress transfer distribution (4). Besides the distribution of mechanical forces, immune reactions in response to the metal instrumentation system can also play a role in the development of pain (11). However, the effect of the load on lumbar degeneration and instrumentation is likely the main source of pain generation; there is little evidence to support the hypothesis that immune system sensitivity to metal occurs leading to the subsequent development of severe pain.…”
Section: █ Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study identified that the most common localization of low back pain after instrumentation was in the sacroiliac joint, likely due to stress transfer distribution (4). Besides the distribution of mechanical forces, immune reactions in response to the metal instrumentation system can also play a role in the development of pain (11). However, the effect of the load on lumbar degeneration and instrumentation is likely the main source of pain generation; there is little evidence to support the hypothesis that immune system sensitivity to metal occurs leading to the subsequent development of severe pain.…”
Section: █ Discussionmentioning
confidence: 99%
“…When the disease is treated surgically, the patient may █ INTRODUCTION E lective lumbar spinal fusion surgery as a treatment for lumbar degenerative disease (LDD) is a common general neurosurgical practice. In the United States alone, over 300,000 lumbar spinal fusion surgeries are performed annually (1,11). Despite this, patients may experience persistent lumbar pain after surgery.…”
mentioning
confidence: 99%
“…Metal can corrode through mechanical movement or through biological interaction. Metal ions liberated by this corrosion can initiate local inflammation (4,24,25). We did not find any data about metal corrosion in the medical records of the patients who undergone reoperations.…”
mentioning
confidence: 82%
“…The strategy of posterior discectomy followed by lumbar fusion and internal xation is commonly adopted to treat patients with lumbar degenerative disease (LDD) (1). In the United States, there are more than 300,000 lumbar fusion operations performed every year (2). With the growing senior population, the incidence of LDD and lumbar fusion operations is expected to persist at a high level (3).…”
Section: Introductionmentioning
confidence: 99%